2020
DOI: 10.21608/ejm.2020.22329.1145
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Green Bean Damping-off Disease Caused by Rhizoctonia solani by Streptomyces parvulus Strain 10d

Abstract: T HIS STUDY aimed to evaluate the efficacy of applying spores and chitinase enzyme of Streptomyces parvulus strain 10d in biological control of damping-off disease caused by Rhizoctonia solani in green beans (Phaseulus vulgaris) and compare it with Rhizolex fungicide application. Five seeds of green bean were sown in plastic pots, filled with either sterilized or non-sterilized soils, infested with R. solani inoculum (5g/kg soil). Pots were kept in the greenhouse for 45 days from sowing. Pre-emergence damping-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…(BCA-546 and CAI-8) significantly reduced charcoal rot in sorghum caused by M. phaseolina under semi-controlled conditions. On the other hand, our results are also in correspondence with those reported by Korayem et al [33] who evaluated the biological activity of S. parvulus strain 10d against R. solani on green beans in a semi-controlled trial with sterilized and non-sterilized soil. These authors showed that seedlings plants treated with a spore suspension of S. parvulus strain 10d showed the highest survival rate (88%) and the lowest DSroot (28%) in the whole of the experiment, showing much better results than those observed for seedlings treated with specific chemicals such as Rhizolex ® [31].…”
Section: Discussionsupporting
confidence: 92%
“…(BCA-546 and CAI-8) significantly reduced charcoal rot in sorghum caused by M. phaseolina under semi-controlled conditions. On the other hand, our results are also in correspondence with those reported by Korayem et al [33] who evaluated the biological activity of S. parvulus strain 10d against R. solani on green beans in a semi-controlled trial with sterilized and non-sterilized soil. These authors showed that seedlings plants treated with a spore suspension of S. parvulus strain 10d showed the highest survival rate (88%) and the lowest DSroot (28%) in the whole of the experiment, showing much better results than those observed for seedlings treated with specific chemicals such as Rhizolex ® [31].…”
Section: Discussionsupporting
confidence: 92%
“…Various methods were reported to control damping-off and root rot diseases in common bean. These methods including cultivate resistant varieties (Brisa et al, 2007 andObala et al, 2012), cultural practices (Abeysinghe, 2007;Abawi andWidmer, 2000 andToledo-Souza et al, 2012), plant extracts Tripathi, 1991 andSoliman et al, 2013), biological control agents (Sallam, Nashwa et al, 2008;Mahamune and Kakde 2011;El-Fiki et al, 2014;Riad et al, 2015;Hussein et al, 2018 andKorayem et al, 2020) and the most effective method is chemical control (Theer, 2012;Buts and Singh, 2014;Elshahawy et al, 2016;Kumar et al, 2019 andKorayem et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%